2020
DOI: 10.1177/0021998320923134
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic wave shielding/absorption performances of cementitious composites incorporating carbon nanotube metamaterial with helical chirality

Abstract: Helical carbon nanotubes, a type of chiral metamaterial, were employed to investigate their effects as well as the mechanisms to electromagnetic wave shielding and absorption performances of cementitious composites over the frequency range from 2 GHz to 18 GHz. The results demonstrate that the best electromagnetic wave shielding effectiveness (SE) of cementitious composites filled with 7.5 wt.% helical carbon nanotubes is 1.39 times of that of cementitious composites without helical carbon nanotubes. The minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Li et al [66] found that smart CFRC mainly affects the reflection loss ratio of electromagnetic wave shielding and dielectric losses absorbed by electromagnetic waves by analyzing the electromagnetic parameters and conductive mechanism. Both parameters are attributed to the increase in carbon fibers to increase the electrical conductivity.…”
Section: Electromagnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [66] found that smart CFRC mainly affects the reflection loss ratio of electromagnetic wave shielding and dielectric losses absorbed by electromagnetic waves by analyzing the electromagnetic parameters and conductive mechanism. Both parameters are attributed to the increase in carbon fibers to increase the electrical conductivity.…”
Section: Electromagnetic Fieldmentioning
confidence: 99%
“…( (2) It is necessary to study the performance stability under the coupling effect of environmental factors during long-term use Smart NCBC Dai Yan Wen et al [112] (3) Loading system, temperature, humidity and other environmental factors greatly influence smart NFRC Smart CNFC Linwei Li et al [66] Chemical field Smart OFRC Self-healing…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Kawashima et al [33] observed that the incorporation of nanoclay into cementitious materials enhances the thixotropic behavior of the mixture. Similarly, nanomaterials such as nanosilica, characterized by strong reactivity and a high specific surface area, can also be utilized to improve the rheological parameters, setting behavior, and mechanical properties of geopolymer materials [34][35][36][37][38]. Nonetheless, the practical application of nanomaterials in geopolymer materials is limited due to their high cost and propensity for aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the dielectric and magnetic absorbing materials, different nano modifiers, can be used. Carbon nanotube (CNTs, MWCNT) [12][13][14][15], carbon black [16,17], activated carbon derived from coconut-fiber [18], carbonyl-iron nano particles [19][20][21][22], iron oxide nanoparticle [23], (Fe‚ Co) oxide nanoparticles [24], Fe 2 O 3 and SiC particle [25], Ni-Zn ferrite [26], copper nanoparticles [27], NiO [28] are some of additives mostly applied for electromagnetic wave absorption. MWCNT [29,30], iron powder [31] are some particles used for mechanical and fracture behavior enhancement.…”
Section: Introductionmentioning
confidence: 99%